PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN KEMAMPUAN BERBAHASA INGGRIS DI KAMPOENG SINAOE SIWALAYANPANJI BUDURAN SIDOARJO - Budi Purwantiningsih (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
Kampoeng Sinaoe Siwalanpanji Buduran Sidoarjo is a non-formal institution that has implemented a contextual learning model with the aim of improving English language skills by relating it to everyday life so that students feel not burdened in learning English which for some people is a difficult subject. This study aims to:  find out the application of contextual learning models, to find out the improvement of English skills using contextual learning models, and  to find out what are the supporting and inhibiting factors of contextual learning in improving English skills in Kampoeng Sinaoe Siwalanpanji Buduran Sidoarjo. The research method used is a phenomenological approach, a type of field research that is descriptive qualitative in nature. The research objects were elementary school students participating in Bronze I and Bronze II from January to February 2020. The results of the study stated that: 1) The application of Contextual Teaching and Learning refers to the main vision of the institution, namely creating a dignified learning society to build national civilization by based on lifelong education (Lifelong Education Based), the application of Contextual Learning does not require large costs and special media is not only related to learning in class, but is related to student experiences that are seen, heard, and felt by students who can change behavior and student learning outcomes. In this case the forms of Contextual Learning that are applied include: a) Providing examples or role models, b) Habituation, c) Motivation, and c) Punishment.  Improving English Proficiency through Contextual Learning through techniques: 1) Field Study (Case Study/direct object) 2) Songs and Games / Teaching English by using song, 3) The Reading Method, 4) Teaching English by using games, 5) Conversation Method. Supporting factors, namely: internal factors consisting of: the existence of social activities, the presence of foreign teachers, schools require teachers to interact with students, and teachers are able to master every school subject and become professional teachers. The external factors are: the existence of a study club, and the support of student guardians